1994
DOI: 10.1073/pnas.91.15.6889
|View full text |Cite
|
Sign up to set email alerts
|

A circularly permuted recombinant interleukin 4 toxin with increased activity.

Abstract: Fusion of ligands such as growth factors to other proteins often dramatically reduces the affinity of the ligand for its receptor. With recombinant DNA techniques, the attachment point between the two proteins has until now been restricted to either the amino or the carboxyl terminus of the d. However, binding may be greatly compromised if both ends are close to the site at which the ligand binds to its receptor. To construct a single-chain growth factor fusion protein with the connection at a new site on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
53
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 39 publications
2
53
0
Order By: Relevance
“…The absence of g c protein indicated that medulloblastoma cell lines express type II IL-4R as do malignant glioma cells. This configuration is similar to that observed on other tumour cells including renal cell carcinoma, AIDS-Kaposi's tumours, head and neck tumours, colon carcinoma, ovarian carcinoma and breast tumour cells (Husain et al, 1997;Kawakami et al, 2000;Kreitman et al, 1994;Leland et al, 2000;Murata et al, 1997b;Puri et al, 1996b).…”
Section: Discussionsupporting
confidence: 85%
“…The absence of g c protein indicated that medulloblastoma cell lines express type II IL-4R as do malignant glioma cells. This configuration is similar to that observed on other tumour cells including renal cell carcinoma, AIDS-Kaposi's tumours, head and neck tumours, colon carcinoma, ovarian carcinoma and breast tumour cells (Husain et al, 1997;Kawakami et al, 2000;Kreitman et al, 1994;Leland et al, 2000;Murata et al, 1997b;Puri et al, 1996b).…”
Section: Discussionsupporting
confidence: 85%
“…IL-4 fused with Pseudomonas exotoxin was delivered to brain tumors and destroyed the brain tumor selectively. 31,32 Chen et al 33 attempted to introduce the membrane translocation domain of Pseudomonas exotoxin A into a DNA delivery vehicle to increase the translocation efficiency of DNA into the cytosol. 34 That work, however, was cell-type dependent.…”
Section: Discussionmentioning
confidence: 99%
“…IL-4R is an ideal candidate for targeted toxin therapy because of its rapid internalisation upon ligand binding and limited expression profile in normal tissues (Kawakami et al, 2002a, b). Numerous preclinical studies have shown the potent anti-tumour activity of a monospecific cytotoxin composed of IL-4 linked to PE38 (Kreitman et al, 1994;Shimamura et al, 2007). However, efficacy of this agent in a Phase I clinical trial of patients with renal cell carcinoma and NSCLC yielded no objective tumour responses, likely because of the rapid development of neutralising antibodies (Garland et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-4 is an important cytokine in Th2 differentiation of T cells and IL-4R has proven to be a promising target for treatment of pancreatic cancer and glioblastoma (Rand et al, 2000;Shimamura et al, 2007). To enhance the activity of cytotoxins targeting IL-4R, a circularly permuted IL-4 cytotoxin has been described that improved binding site exposure without altering ligand-receptor specificity (Kreitman et al, 1994) and these alterations were incorportated into EGF4KDEL. Both EGFR and IL-4R are ideal targets for liganddirected toxin therapies as both are cell surface molecules that internalise rapidly upon ligand binding (Haigler et al, 1978;Kawakami et al, 2002a).…”
mentioning
confidence: 99%